Computer security -- ESORICS 2016. 21st European Symposium on Research in Computer Security, Heraklion, Greece, September 26-30, 2016, Proceedings /: 21st European Symposium on Research in Computer Security, Heraklion, Greece, September 26-30, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available